Quantitative analysis of mortar waste in civil construction in Brazil between the years 2009 and 2018 - Gabriel Sousa de Freitas; Fabrício Bau Dalmas (Revista Principia, 2022)
Civil construction is one of the main generators of economic and social development in Brazil. However, due to the way it is executed, it is also one of the sectors that causes the most environmental impacts at all stages of its production chain: extraction of raw materials; industrialization; commerce and services; and generation of waste that can cause damage to the environment. The inadequate final disposal of civil construction or demolition waste can generate major environmental impacts, such as soil, river, and air pollution. Considering this context, in the present research, a survey was conducted on the disposal of mortars collected on public roads in all Brazilian municipalities from 2009 to 2018. The analysis used data from Associação Brasileira de Empresas de Limpeza Pública e Resíduos Especiais. It was discovered that, between 2009 and 2018, 1,142,065 T/day of civil construction waste were collected and that the largest amount of this waste was mortar, with 719,501 T/day discarded on public roads in Brazil. Recycling this waste would be a solution for the mitigation of environmental damage caused by improper disposal and, consequently, would contribute to the preservation of the environment.